Surface Roughness Effects on Turbulent Boundary Layer Struc-ture of NACA 0026 Airfoil - Abbas, A. A.; Ghopa, W. A. W.; Mat, S.; Choi, K.-S.; Abdullah, M. F.; Harun, Z. (International Journal of Engineering and Technology, 2018)
This research addresses the understanding of initial experimental results from an ongoing investigation of the riblets effects on the behaviour of turbulent boundary layer over a rough surface applied onto the surface of NACA 0026 airfoil in a herringbone pattern, via a low-speed wind tunnel. Riblets arranged in directionally converging-diverging pattern, approximately 7.5% in chord percentage, riblets are attached and flushed to the airfoil surface. Riblets are yawed at α = 0o and ±10o with dimensions of height, h = 1 mm and spacing, s = 2 mm. The airfoil with external geometry of 500 mm span, 600 mm chord, and 156 mm maximum thickness has been built using mostly woods and aluminium. The application of riblets significantly affects boundary layer thickness. At Reynolds number Reτ ≈ 200 and freestream velocity U∞ ≈ 5 m/s. We observe that riblets cause boundary layer and turbulence intensities profiles to change drastically. Upon exposure to riblets, both boundary layer and turbulence intensities profiles on NACA 0026 airfoil follow closely with that of favourable pressure gradient (FPG) flows. Without riblets, the flow has a very small layer of the logarithmic region and high wake (in the velocity profile) and highly energized inner region (in the intensities profiles). Without riblets, the inner region (z+ = 15) contains energised λx+ = 1000 features as well as very long features measuring 20δ, typically not observed in internal flows. The energy spectra analysis reveals that riblets of any type break these 20δ features in the near-wall to break down into smaller features. This study might shed some lights into research focusing on controlling flow behaviours using surface roughness.